2022
DOI: 10.1128/spectrum.02005-22
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Sulfadoxine-Pyrimethamine Resistance in Plasmodium falciparum Isolates from Central Africa between 2016 and 2021: Wide Geographic Spread of Highly Mutated Pfdhfr and Pfdhps Alleles

Abstract: Monitoring drug resistance is important for malaria control because its early detection enables timely action to prevent its spread and mitigate its impact. The wide geographic spread and the increasing trend of highly resistant Pfdhfr genes between 2016 and 2021 found in our study are worrisome and emphasize the urgency to monitor their updated status in central Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Moreover, the novel Pfdhps I 431 V allele previously detected in Nigeria and observed to be spreading across Central Africa ( 25 , 26 ) including Chad and the Democratic Republic of Congo was identified in this study at a frequency of 27.1%. This allele exhibited similar frequency (30.8%) in the H/T and human stages although lower in the midgut stage (18.1%), possibly because of sporozoite population expansion in the salivary gland from ruptured oocyst that successfully traversed the midgut barrier ( 20 ).…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, the novel Pfdhps I 431 V allele previously detected in Nigeria and observed to be spreading across Central Africa ( 25 , 26 ) including Chad and the Democratic Republic of Congo was identified in this study at a frequency of 27.1%. This allele exhibited similar frequency (30.8%) in the H/T and human stages although lower in the midgut stage (18.1%), possibly because of sporozoite population expansion in the salivary gland from ruptured oocyst that successfully traversed the midgut barrier ( 20 ).…”
Section: Discussionsupporting
confidence: 57%
“…The Pfdhfr mutant alleles N51I, C59R, and S108N have been found to be highly prevalent and widespread in Africa, as well as the triple mutant Pfdhfr I 51 R 59 N 108 haplotype. Almost all had a prevalence of over 90% 17,[24][25][26][27] . Previous research also showed the mutant Pfdhfr I164L had a high frequency in Asia, with relatively low prevalence in Africa [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have indicated that SP resistance is related to mutations at codons S436A/F, A437G, K540E, A581G, and A613S/T in Pfdhps genes and N51I, C59R, S108N, and I164L in Pfdhfr genes [10][11][12][13] . A novel mutation I431V in Pfdhps genes was rst detected in Nigeria in 2007, then in some other countries of West and Central Africa [14][15][16][17] . In most cases, the mutation I431V occurs simultaneously with four other Pfdhps mutations: S436A, A437G, A581G, and A613S, forming a quintuple mutant V 431 A 436 G 437 K 540 G 581 S 613 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation